Answer:
2(2x-2.5)
4(x-1.25)
5(0.8x-1)
Step-by-step explanation:
Answer:
dy/dx = (x^2 - 3)^sin x [2x sin x/ (x^2 - 3) + cos x ln(x^2 - 3)]
Step-by-step explanation:
y = (x^2 - 3)^sinx
ln y = ln (x^2 - 3)^sinx
ln y = sin x * ln (x^2 - 3)
1/y * dy/dx = sin x * {1 / (x^2 - 3)} * 2x + ln(x^2 - 3) * cos x
1/y dy/dx = 2x sin x/ (x^2 - 3) + cos x ln(x^2 - 3)
dy/dx = [2x sin x/ (x^2 - 3) + cos x ln(x^2 - 3)] * y
dy/dx = (x^2 - 3)^sin x [2x sin x/ (x^2 - 3) + cos x ln(x^2 - 3)]
Quadratic is in the form
ax^2+bx+c=0
so distribute and stuff and simplify
remember
a(b+c)=ab+ac
(x+2)^2+5(x+2)-6=0
remember order of opertaions
(x+2)(x+2)+5(x+2)-6=0
x^2+4x+4+5x+10-6=0
add like terms
x^2+9x+8=0
Answer:
Truth plz
Step-by-step explanation: